Effect of Ovarian Changes according to Four Season for Reproduction of Jeju Crossbred Horses - Yeong-Ju Yu; Seol-Hwa Park; Sang-Min Shin; Byoung-Chul Yang; Pil-Nam Seong; Jae-Hoon Woo; Nam-Young Kim; Jun-Kyu Son (The Korean Society of Animal Reproduction and Biotechnology, 2017)
This study was conducted to investigate the ovarian cycle changes of the mare according to the season. Twenty four Jeju crossbred horses(Thoroughbred x Jeju horse) raised in Subtropical Livestock Research Institute, National Institute of Animal Science, RDA were used to identify follicles and corpus luteum with ultrasonography once a week(May 2016~June 2017). Blood samples of experimental horses were collected twice a week for analysis of P4 hormone levels. The mares were considered to have resumed ovarian cyclicity on the day of ovulation if they followed by regular ovarian cycles. Only 13 cases(61.9%) of the total 21cases showed normal ovarian cycle, and 8 cases (38.1%) showed delayed ovarian cycle. Three cases(16.7%) in October, 5 cases(27.8%) in November and 5 cases(27.8%) in December(27.8%) ceased the heat and the remaining 5 cases(27.8%) showed that the estrus was maintained in winter. Horses that stopped estrus ceased the heat until March of next year, and 27.8% were continued the heat during non-breeding season. Eleven cases(61.1%) of 18 cases in April and 2 cases(11.1%) of 18 cases in May returned the estrus.